1997
DOI: 10.1104/pp.114.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate-Inducible Genes Are Activated in Rice by Pathogen Attack without a Concomitant Increase in Endogenous Jasmonic Acid Levels

Abstract: Jersey 08903-0231 (P. Silverman, M.S., I.R.)The possible role of the octadecanoid signaling pathway with jasmonic acid (JA) as the central component i n defense-gene regulation of pathogen-attacked rice was studied. Rice (Oryza sativa 1.) seedlings were treated with JA or inoculated with the rice blast fungus Magnaporthe grisea (Hebert) Barr., and gene-expression patterns were compared between the two treatments. JA application induced the accumulation of a number of pathogenesis-related (PR) gene products at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 34 publications
5
64
0
4
Order By: Relevance
“…This apparent paradox remains to be clarified, since MeJA is suggested to play a role in plant-defense responses (Coehn et al, 1993;Mueller et al, 1993;Reinbothe et al, 1994). Nevertheless, no correlation could be found between jasmonates and defense responses in plant-pathogen interactions (Schweizer et al, 1993;Kogel et al, 1995;Schweizer et al, 1997). How coronatine could function as a virulence factor by mimicking MeJA in a bacteria-plant interaction is an open question.…”
mentioning
confidence: 99%
“…This apparent paradox remains to be clarified, since MeJA is suggested to play a role in plant-defense responses (Coehn et al, 1993;Mueller et al, 1993;Reinbothe et al, 1994). Nevertheless, no correlation could be found between jasmonates and defense responses in plant-pathogen interactions (Schweizer et al, 1993;Kogel et al, 1995;Schweizer et al, 1997). How coronatine could function as a virulence factor by mimicking MeJA in a bacteria-plant interaction is an open question.…”
mentioning
confidence: 99%
“…9,10) Wounding causes a strong and transient accumulation of JA, followed by the induction of a number of pathogenesis-related (PR) genes, in the treated leaf. 11) Thus the expression profiles of Xip-I obtained in this study, viz., wound-, MeJA-, and pathogen-inducibility, indicate that Xip-I is a PR gene involved in plant defense.…”
mentioning
confidence: 99%
“…In other plant systems similar phenomena have been reported. For instance, Schweizer et al [41] demonstrated that during infection of rice with the fungal pathogen Magnaporthe grisea, jasmonate-inducible genes are activated without an increase in endogenous JA levels. Moreover, Tsai et al [47] provided evidence that an increase in ethylene sensitivity rather than ethylene production is the initial event in triggering JA-enhanced senescence in detached rice leaves.…”
Section: Introductionmentioning
confidence: 99%